Personality traits can predict which exercise intensities we enjoy most, and the magnitude of stress reduction experienced following a training program - Flaminia Ronca; Benjamin Tari; Cian Xu; Paul W. Burgess (Frontiers in Psychology)
IntroductionThe aim of this study was to determine if personality can predict physical fitness, enjoyment of exercise by intensity, and engagement in an exercise program in the general population.MethodsParticipants were assigned to either an 8-week home-based cycling and strength training intervention or a resting control group.ResultsPersonality traits were strong predictors of baseline fitness levels, and of enjoyment of different exercise intensities. For example, conscientiousness predicted greater general fitness and more weekly hours of physical activity, whereas extraversion and neuroticism predicted higher V̇O2peak and poorer heart rate recovery, respectively. Extraversion also predicted greater enjoyment of highest intensity activities, whereas neuroticism predicted lower enjoyment of activities which required sustained effort. Importantly, those who scored high on neuroticism benefited the most from potential stress-reducing effects of aerobic training.DiscussionThese findings provide insight into how personality can determine engagement with physical activity, and the degree to which one enjoys different forms of exercise, thus aiding the development of tailored exercise programs.